1993
DOI: 10.1128/aac.37.2.246
|View full text |Cite
|
Sign up to set email alerts
|

Roles of liposome composition and temperature in distribution of amphotericin B in serum lipoproteins

Abstract: The role of liposome composition and temperature in the distribution of amphotericin B (AmB) with serum lipoproteins and the role of particle charge in AmB transfer to serum lipoproteins were determined. Serum obtained from healthy volunteers was incubated with known concentrations of AmB or different liposomal formulations of AmB (1 to 100 ,ug/ml) at 37°C for various time intervals (5, 10, 20, 30, 45, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
1
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 18 publications
1
69
1
3
Order By: Relevance
“…Outros estudos avaliaram a interação de AB com lipoproteínas e mostraram que a alteração da composição lipídica vascular levou a redução dos efeitos tóxicos de AB-DOC (Wasan et al, 1993;Wasan et al, 1994;Chavanet et al, 1994;Marzzullo et al, 1996), na presença de lipoproteínas a forma livre de AB apresentou-se reduzida e sua concentração foi menor quando as lipoproteínas foram obtidas de soro pós-prandial, demonstrando que a dieta influenciou na quantidade de fármaco livre tóxico (Chavanet et al, 1994). Assim, a associação de AB com diferentes frações do plasma, assim como sua maior solubilização nestas frações, pode ser um fator responsá-vel pela redução da toxicidade do antifúngico.…”
Section: Mecanismos Propostos Para Redução De Toxicidadeunclassified
See 1 more Smart Citation
“…Outros estudos avaliaram a interação de AB com lipoproteínas e mostraram que a alteração da composição lipídica vascular levou a redução dos efeitos tóxicos de AB-DOC (Wasan et al, 1993;Wasan et al, 1994;Chavanet et al, 1994;Marzzullo et al, 1996), na presença de lipoproteínas a forma livre de AB apresentou-se reduzida e sua concentração foi menor quando as lipoproteínas foram obtidas de soro pós-prandial, demonstrando que a dieta influenciou na quantidade de fármaco livre tóxico (Chavanet et al, 1994). Assim, a associação de AB com diferentes frações do plasma, assim como sua maior solubilização nestas frações, pode ser um fator responsá-vel pela redução da toxicidade do antifúngico.…”
Section: Mecanismos Propostos Para Redução De Toxicidadeunclassified
“…Assim, a associação de AB com diferentes frações do plasma, assim como sua maior solubilização nestas frações, pode ser um fator responsá-vel pela redução da toxicidade do antifúngico. Wasan et al (1993) realizaram diversos experimentos para elucidar a diminuída toxicidade de AmBisome em consideração à associação de AB com lipoproteínas. Seus resultados mostraram que modificações na temperatura e na composição lipídica do lipossoma implicaram alteração na distribuição da AB entre HDL e LDL.…”
Section: Mecanismos Propostos Para Redução De Toxicidadeunclassified
“…However, the pharmacokinetics, tissue distribution, and extents of nephrotoxic effects of L-AmpB in diabetic rats were unchanged (20). In addition, we have demonstrated that AmpB associates predominantly with high-density lipoproteins (HDL) following a 1-h incubation at 37°C in human serum, and the amount of AmpB associated with HDL increases when AmpB is incorporated into negatively charged liposomes composed of DMPC and DMPG (17 animals were allowed to recover for 48 h after the surgical procedure. Water and rat chow (Ralston Purina Co., St. Louis, Mo.)…”
mentioning
confidence: 93%
“…Судьба лекарств, снабжённых наносистемами транспорта, в кровотоке определяется их взаимодействием с компонентами крови, клетками тканей-мишеней и здоровых тканей [3][4][5][6]. Для опухолевых тканей и областей воспаления характерен "эффект повышенной проницаемости и удерживания" (enhanced permeability and retention, EPR) [7].…”
Section: Introductionunclassified